Role of Relational Capabilities on the Supply Chain Performance of Indonesian Textile Sector with Moderating Effect of Technology Adoption - Andhyka Tyaz Nugraha; Yusro Hakimah (International Journal of Supply Chain Management, 2019)
In modern era dynamic business environment has been changed. In these days competition is no longer between organizations, but between supply chains. The supply chain dependency leads the business focused on supply chain performance. The objective of this study is to examine the influence of relational capabilities on the supply chain performance of Indonesian. This study also intended to investigate the moderating role of technology adoption on the relationship between relational capabilities on the supply chain Performance. To fulfil the objectives of this study, the data was collected from the managing directors, supply chain managers, planning managers, and procurement managers. Structure Equation Modelling was applied for the assessment of hypotheses. This study’s findings show that supplier partnership, customer relationship and information sharing significantly influence the supply chain performance of Indonesian textile companies. Results also indicated that technology adoption has moderating effect on the relationship between supplier partnership, and information sharing with supply chain performance of Indonesian textile companies. Additionally, results indicate that technology adoption has no moderating role on the relationship of customer relationship with supply chain performance. This study contributes to Supply chain Management literature and provides empirical evidence that relational capabilities are those factors that could enhance supply chain performance of the firms with technology adoption.